Technology evolution and application innovation of industrial PON - ZENG Tao; JIANG Ming; ZHANG Dezhi; YANG Ziyao (Dianxin kexue, 2024)
Along with the country’s vigorous promotion of new infrastructure construction and the rapid development of industrial Internet, industrial passive optical network (PON) technology is increasingly widely used in the industrial field. The policy background of industrial PON technology development was discussed in depth, its key technologies in broadband enhancement, network protection, deterministic delay, open intelligence, and security protection were elaborated, and the application practice of industrial PON in typical business scenarios was analyzed.